A Simple Risk Score for Predicting Neurologic Outcome in Out-of-Hospital Cardiac Arrest Patients After Targeted Temperature Management*. Issue 3 (8th September 2021) - Chen, Chung-Ting; Lin, Jin-Wei; Wu, Cheng-Hsueh; Kuo, Raymond Nien-Chen; Shih, Chia-Hui; Hou, Peter Chuanyi; Yen, David Hung-Tsang; How, Chorng-Kuang
Abstract : OBJECTIVES: Although several risk factors for outcomes of out-of-hospital cardiac arrest patients have been identified, the cumulative risk of their combinations is not thoroughly clear, especially after targeted temperature management. Therefore, we aimed to develop a risk score to evaluate individual out-of-hospital cardiac arrest patient risk at early admission after targeted temperature management regarding poor neurologic status at discharge. DESIGN: Retrospective observational cohort study. SETTING: Two large academic medical networks in the United States. PATIENTS: Out-of-hospital cardiac arrest survivors treated with targeted temperature management with age of 18 years old or older. INTERVENTIONS: None. MEASUREMENTS AND MAIN RESULTS: Based on the odds ratios, five identified variables (initial nonShockable rhythm, Leucocyte count < 4 or > 12 K/μL after targeted temperature management, total Adrenalin [epinephrine] ≥ 5 mg, lack of oNlooker cardiopulmonary resuscitation, and Time duration of resuscitation ≥ 20 min) were assigned weighted points. The sum of the points was the total risk score known as the SLANT score (range 0–21 points) for each patient. Based on our risk prediction scores, patients were divided into three risk categories as moderate-risk group (0–7), high-risk group (8–14), and very high-risk group (15–21). Both the ability of our risk score to predict the rates of poor neurologic outcomes at discharge and in-hospital mortality were significant under the Cochran-Armitage trend test ( p < 0.001 and p < 0.001, respectively). CONCLUSIONS: The risk of poor neurologic outcomes and in-hospital mortality of out-of-hospital cardiac arrest survivors after targeted temperature management is easily assessed using a risk score model derived using the readily available information. Its clinical utility needed further investigation.